HYGIENE IN WORLD HISTORY. - STEARNS, PETER N.
1 online resource (176 pages)
Keywords: This book features a global, historical analysis of the changes and continuities in one of society's basic functions: seeking to protect itself from disease.Hygiene offers an important lens for major aspects of world and comparative history. The volume explores the ways different regions and major religions approached hygiene both before modern times and through the present with the more recent uses of germ theory. Topics in "premodern" hygiene include toilet practices, remarkably varied views about bathing, and different levels of commitment to investments in hygiene infrastructure. The "sanitary revolution" of the nineteenth and twentieth centuries forms a major dividing line in the book, including the variations introduced by developments like colonialism or communism and various forms of resistance to "modern" hygiene. The book links current, often bitter, debates about hygiene, around practices such as masking, both to the larger history and to recent issues like COVID-19.Hygiene in World History is an accessible overview aimed at undergraduate and non-specialist readers interested in world history, public health, and the history of health and disease.